Alexander Hume-Campbell, Earl of Marchmont, papers - Marchmont, Alexander Hume-Campbell, Earl of, 1675-1740.
Transcripts made for Marchmont of papers relating to British revenue (1662-1721), the national debt (1735-1738), and the military (1662-1740).
Transcripts (handwritten)
British peer and diplomat. Also known as Lord Polwarth.
Collection material in English.
Keywords: Diplomatic and consular service, British -- 18th century; Finance -- Great Britain; Debts, Public -- Great Britain; Great Britain -- Military policy; Great Britain -- Economic conditions -- 17th century; Great Britain -- Economic conditions -- 18th century; Great Britain -- Politics and government -- 1603-1714.; Great Britain -- Politics and government -- 18th century; Diplomats -- Great Britain